DARI PAPARAN MENUJU PENGALAMAN: PENENTU KEPUASAN PELANGGAN DAN NIAT PEMBELIAN ULANG DALAM KONSUMSI TEH SUSU ARTISAN - Kevin Gustian Yulius; Vasco Adato Haholongan Goeltom; Yosep Dudedes Timba (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2026)
This study examined the determinants of customer satisfaction and repurchase intention in artisan milk tea consumption within a contemporary F&B service context. The research addressed four key problems: the effects of social media exposure, perceived product quality, and experiential value on customer satisfaction, as well as the effect of customer satisfaction on repurchase intention. A quantitative approach with a causal hypothesis design was employed, using data collected from 160 respondents through an online questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicated that social media exposure, perceived product quality, and experiential value all had positive and significant effects on customer satisfaction. Furthermore, customer satisfaction showed a strong and significant effect on repurchase intention. These findings suggested that consumer behavior in artisan milk tea consumption was shaped by the integration of digital engagement, product quality, and experiential factors. The study contributed to the understanding of experiential consumption in the F&B industry and provided practical insights for businesses in developing strategies to enhance customer satisfaction and encourage repeat purchasing behavior.